MAá¸¤MÃ›D ABÃ› RAYYAH DAN KRITISISME HADIS - Anam, Wahidul (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2016)
Ma?mûd Abû Rayyah comes to the study of ?adîth as a controversial scholar. His criticism has made a significant change in modern period in which his critics are directed towards some literatures and early ?adîth scholars (râwî). One of the making polemic in his study is his critical study on the authenticity of ?adîth in Bukhârî?s book, ?ahî? Bukhârî. It is not only Bukhârî whom his critics are pointed out, but also Abû Hurayrah, a person who has narrated so many ?adîth and become the most cited name in ?adîth literatures. This paper would shed light on the epistemological view of Abû Rayyah in ?adîth criticism. It highlights three branches of ?adîth studies: authenticity, reliability and historical analysis. This study suggests that Abû Rayyah put al-sunnah al-hudâ (a living tradition of Mu?ammad which is related to ?aqîdah and sharî?ah) as a main tool for validity to determine the authenticity of ?adîth. In this case, every ?adîth which contradicts to this value should be rejected. Further he said that ?adîth codification did not take place in the period prior to al-Zuhrî. The political pressure is one of the reasons why al-Zuhrî and other Muslims are militant to write and collect Mu?ammad traditions of ?adîth.